Isolated anterior-chamber fungal flocculosus in a healthy child with seeding through the trabecular meshwork - Manjula Jayakumar; Akshaya Parthasarathy (TNOA Journal of Ophthalmic Science and Research, 2019)
We report a case of isolated anterior-chamber (AC) fungal hyphae in a healthy child following injury with a broomstick with no evidence of obvious intraocular penetration, a rare presentation of isolated traumatic AC mycoses. In our case, although there was no obvious intraocular penetration, a broom bristle could have injured the trabecular meshwork acting as a conduit for the seeding of the fungal growth. Ours is a peculiar case of seeding through the trabecular meshwork so far not cited in literature.